QUALITY OF LIFE AMONG PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE ATTENDING IN MEDICAL OPD OF CHITWAN MEDICAL COLLEGE, CHITWAN - Chapagain , Shakuntala; Paudel , Binaya; Paudel , Isha; Khanal , Dina; Koirala , Subash; Chhetri , Mamta; Khanal , Gayatri; Shrestha , Sarbada (Journal of Chitwan Medical College, 2022)
Background: Chronic obstructive pulmonary disease is a major cause of morbidity and mortality worldwide which can severely impair the individual’s quality of life. The study aimed to assess the quality of life of patients having chronic obstructive pulmonary disease. Methods: A cross-sectional hospital-based study was conducted in medical OPD of Chitwan Medical College. Purposive sampling technique was used to select 203 patients with chronic pulmonary obstructive disease for at least 3 months. Data were collected from July 16, 2021 to January 14, 2022 using a WHO Quality of Life Scale-Brief through face-to-face interview. Transformation of the scores was done to standardize the raw scores by using the formula applied for linear transformation is as follows: [(Actual raw score - Lowest possible raw score)/Possible raw score range]*100. Results: The mean score and standard deviation of total QOL was 40.64 ± 18.41, where 52.23 ± 13.68 for physical, 47.84 ± 9.70 for psychological, 66.63 ± 9.25 for social and 54.62 ± 13.44 for environment domain showing higher impairment in psychological. Sex (0.031), type of family (0.042), educational status (<0.001), smoking habit (0.005) and duration of COPD (<0.001) were found statistically significant with total QOL of COPD patient. Conclusions: This study showed an impaired quality of life in COPD patients. Longer disease duration and smoking habit of patient impacted negatively on their QOL. Hence, attention should be paid by health professional for enhancing QOL by addressing those factors while treating them in health care setting